The putative Leishmania telomerase RNA (leishTER) undergoes trans-splicing and contains a conserved template sequence - Vasconcelos, Elton J. R.; Nunes, Vinicius S. [UNESP]; Silva, Marcelo S. da [UNESP]; Segatto, Marcela [UNESP]; Myler, Peter J.; Cano, Maria Isabel N. [UNESP] (Public Library Science, 2014)
Telomerase RNAs (TERs) are highly divergent between species, varying in size and sequence composition. Here, we identify a candidate for the telomerase RNA component of Leishmania genus, which includes species that cause leishmaniasis, a neglected tropical disease. Merging a thorough computational screening combined with RNA-seq evidence, we mapped a non-coding RNA gene localized in a syntenic locus on chromosome 25 of five Leishmania species that shares partial synteny with both Trypanosoma brucei TER locus and a putative TER candidate-containing locus of Crithidia fasciculata. Using target-driven molecular biology approaches, we detected a similar to 2,100 nt transcript (LeishTER) that contains a 5'spliced leader (SL) cap, a putative 3'polyA tail and a predicted C/D box snoRNA domain. LeishTER is expressed at similar levels in the logarithmic and stationary growth phases of promastigote forms. A 5'SL capped LeishTER co-immunoprecipitated and co-localized with the telomerase protein component (TERT) in a cell cycle-dependent manner. Prediction of its secondary structure strongly suggests the existence of a bona fide single-stranded template sequence and a conserved C[U/C]GUCA motif-containing helix II, representing the template boundary element. This study paves the way for further investigations on the biogenesis of parasite TERT ribonucleoproteins (RNPs) and its role in parasite telomere biology.